Diseño de una planta de tratamiento de aguas para lavado automotor, para la empresa Translogam S.A.S. (2017)
The present project consists of the design of a water treatment plant to reuse the water used in car washes. A field work was carried out in order to know the current situation of the washing processes in the city of Girardot, in the same way that the fieldwork contributed to the parametrization of key aspects in the design of the plant as it is the flow And the amount of water to be treated. Design alternatives were proposed for a correct treatment of the water, and then execute a detailed design of the processes that make up the water treatment. The engineering design includes the selection of commercial components, the corresponding analytical calculations of structures such as the settler and the hydraulic calculations of losses in pipes, fittings and pump power required in the treatment system. The systems that compose the plant were modeled in the Solid Edge software and to verify the analytical calculations, the finite element software NX 9.0 Finally, the manuals for the installation, operation and maintenance of the equipment that compose the plant were realized.